Maximizing the benefit of health workforce secondment in Botswana: an approach for strengthening health systems in resource-limited settings - Grignon JS; Ledikwe JH; Makati D; Nyangah R; Sento BW; Semo B (Dove Medical Press, 2014)
Jessica S Grignon,1,2 Jenny H Ledikwe,1,2 Ditsapelo Makati,2 Robert Nyangah,2 Baraedi W Sento,2 Bazghina-werq Semo1,2 1Department of Global Health, University of Washington, Seattle, WA, USA; 2International Training and Education Center for Health, Gaborone, Botswana Abstract: To address health systems challenges in limited-resource settings, global health initiatives, particularly the President's Emergency Plan for AIDS Relief, have seconded health workers to the public sector. Implementation considerations for secondment as a health workforce development strategy are not well documented. The purpose of this article is to present outcomes, best practices, and lessons learned from a President's Emergency Plan for AIDS Relief-funded secondment program in Botswana. Outcomes are documented across four World Health Organization health systems' building blocks. Best practices include documentation of joint stakeholder expectations, collaborative recruitment, and early identification of counterparts. Lessons learned include inadequate ownership, a two-tier employment system, and ill-defined position duration. These findings can inform program and policy development to maximize the benefit of health workforce secondment. Secondment requires substantial investment, and emphasis should be placed on high-level technical positions responsible for building systems, developing health workers, and strengthening government to translate policy into programs. Keywords: human resources, health policy, health worker, HIV/AIDS, PEPFAR